Silicosis mortality in Spain (1999–2020): A temporal and geographical approach - Germán Sánchez-Díaz; Greta Arias-Merino; Elisa Gallego; Rodrigo Sarmiento-Suárez; Verónica Alonso-Ferreira (AIMS Public Health)
Background Silicosis is an occupational respiratory disease linked to silica dust inhalation. The main driver was traditional coal mining, but in recent decades, new sources of exposure have emerged. Our aim in this study was to assess the temporal and spatial distribution of mortality due to this disease over a 22-year period in Spain.